Human resource management at 'AD Imlek Belgrade' - Samardžić Maja; Živković Dragić; Rajić Zoran; Jelić Sreten (Ekonomika Poljoprivrede (1979), 2016)
Human resources include overall human potential within an organization: the available knowledge and experience, usable skills and abilities, possible ideas and creations, the level of motivation and interest in the achievement of organizational objectives, etc. The objective of this paper is to highlight the role and importance of human resource management (HRM) in achieving business success, based on the analysis of the most important theoretical and practical aspects of human resource management at the 'Imlek' Company. This study required the use of different methods and techniques such as: content analysis, case study, observation, testing and systemic approach. The study showed that sale of the Imlek Company products was widespread in the country and the region. An ongoing market advantage is achieved due to a high quality standard of products, and primarily due to an effective management of human resources. Company management should make formalization and unification, and implement a set of measures in order to improve discipline of the employees. Top workers should be motivated through incentives for performance and innovation.